2002
DOI: 10.1080/1461380022000011911
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into Children's Responses through Drawing, to Short Musical Fragments and Complete Compositions

Abstract: This paper is taken from a doctoral research project, which investigated children's graphic notations as a representation of their musical perception. One of the main goals of this study was to test empirically the widespread hypothesis that there is a connection between fragmental and contextual perception of music. Graphic notations of 112 Israeli children (aged 7-8.5) in response to musical stimuli that included short musical phrases and complex classical repertoire were examined. Thirteen tasks were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 10 publications
1
27
0
3
Order By: Relevance
“…Elkoshi 2002Elkoshi , 2004aElkoshi , 2004b. The MSC method of analysis is based on a procedure progressing consistently in three phases: Phase 1: The Morphological Analysis (M), which engages in material measures and descriptions of visual phenomenon (e.g.…”
Section: Data Collection and Methods Of Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Elkoshi 2002Elkoshi , 2004aElkoshi , 2004b. The MSC method of analysis is based on a procedure progressing consistently in three phases: Phase 1: The Morphological Analysis (M), which engages in material measures and descriptions of visual phenomenon (e.g.…”
Section: Data Collection and Methods Of Analysismentioning
confidence: 99%
“…This kind of research has generally involved the presentation of familiar and unfamiliar songs and melodies, music composed by children or by adults and classical selections (e.g. Barrett 1997Barrett , 1999Barrett , 2000Barrett , 2001Barrett , 2006Blair 2006;Cohen 1985;Davidson and Colley 1987; 1992; Davidson, Scripp, and Welsh 1988;Elkoshi 2002Elkoshi , 2008Elkoshi, Murphy, and Burnard 2007;Elkoshi et al 2008;Fung and Gromko 2001;Gromko andPoorman 1998a, 1998b;Gromko and Russell 2002;Hair [1993Hair [ ] 1994Kerchner 2001;Shockley 2006;Tan and Kelly 2004;Truman 2007).…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…As far as task variables are concerned, it has been found repeatedly that children's notations are influenced by the kind of sonic or musical material that is presented to them. Several studies have shown that it makes a distinction whether listeners must generate an external representation of a short and isolated sequence of sonic stimuli as against representing a long and/or complex piece of music (Barrett, 1997;Elkoshi, 2002;Verschaffel et al, 2010). Furthermore, it also makes a difference whether listeners are invited to represent fragments that are familiar or unfamiliar-e.g., familiar melodies are "recognized" rather than "experienced," with the notation serving merely as a prompt for memory (Upitis, 1992)-and whether the fragment being heard is accompanied by lyrics or not, as lyrics seem to direct the process of sense-making rather heavily to that aspect (see Barrett, 2002).…”
mentioning
confidence: 97%
“…Several researchers have suggested major distinctions and categories for classifying this wide variation in notations (see e.g., Bamberger, 1980Bamberger, , 1982Bamberger, , 1991Barrett, 2002;, 1989Elkoshi, 2002Elkoshi, , 2004Upitis, 1987Upitis, , 1993 for an overview of the major categorizations and for an attempt at a synthesis, see Reybrouck, Verschaffel, & Lauwerier, 2009;Verschaffel, Reybrouck, Janssens, & Van Dooren, 2010). An important distinction is the difference between global notations, with the fragment being represented in a holistic way by one overall pictorial image-such as a picture of a real-world scene or a person showing a certain emotion-and differentiated notations, which try to capture one or more sonic parameters in their temporal unfolding-such as an informal or standard notation of the actual development of the frequency, duration, and/or amplitude of the incoming acoustic signals (Reybrouck et al, 2009;Verschaffel et al, 2010).…”
mentioning
confidence: 98%
See 1 more Smart Citation